2003
DOI: 10.1007/s00330-002-1565-1
|View full text |Cite
|
Sign up to set email alerts
|

31P-MR spectroscopy in children and adolescents with a familial risk of schizophrenia

Abstract: Based on a previous report [9] on alterations of membrane phosphorus metabolism in asymptomatic family members of schizophrenic patients, the aim of the present study was to extend and improve the evaluation and data processing of 31 P spectroscopic data obtained from a larger study population by including an analysis of the broad spectral component (BC) of membrane phospholipids (PL). Eighteen children and siblings of patients with schizophrenia and a gender-and agematched control group of 18 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 32 publications
0
2
1
1
Order By: Relevance
“…Using the same 31 P MRS approach in chronic patients with schizophrenia, we did not previously find a decrease in PCr, suggesting that this abnormality may be present early in illness. Prior studies examining 31 P MRS measures in unaffected relatives, namely children, of patients with schizophrenia (Keshavan et al, 2003; Klemm et al, 2001; Rzanny et al, 2003), have not reported significant alterations in PCr, ATP or Pi; these studies showed abnormalities in phospholipid metabolites, which we did not find. However, 1 H MRS studies in unaffected relatives of patients with schizophrenia have revealed decreases in PCr and Cr in different brain regions, including the striatum (Keshavan et al, 2009) and thalamus (Yoo et al, 2009).…”
Section: Discussioncontrasting
confidence: 91%
“…Using the same 31 P MRS approach in chronic patients with schizophrenia, we did not previously find a decrease in PCr, suggesting that this abnormality may be present early in illness. Prior studies examining 31 P MRS measures in unaffected relatives, namely children, of patients with schizophrenia (Keshavan et al, 2003; Klemm et al, 2001; Rzanny et al, 2003), have not reported significant alterations in PCr, ATP or Pi; these studies showed abnormalities in phospholipid metabolites, which we did not find. However, 1 H MRS studies in unaffected relatives of patients with schizophrenia have revealed decreases in PCr and Cr in different brain regions, including the striatum (Keshavan et al, 2009) and thalamus (Yoo et al, 2009).…”
Section: Discussioncontrasting
confidence: 91%
“…For 3D localization of in vivo 31 P‐MRS data, ISIS has been used previously with voxel volumes (15–192 ml) and measurement times (3–38 min) at 1.5 T (32, 33), 3 T (34), and at 7 T (15). Nominal spatial resolutions of 4–24 mL, and total measurement times of 8–45 min, were reported for 3D‐CSI at 1.5 T (35), 3 T (17, 34), 4 T (36), and 7 T (6, 25).…”
Section: Discussionmentioning
confidence: 99%
“…In the German HRS, HR had significantly lower mean bilateral prefrontal ratios of PMEs to PDEs (0.25 vs. 0.31) and higher mean PDE values (37.59% vs. 34.87%) than controls, suggesting greater prefrontal phospholipid breakdown in HR subjects [Klemm et al, ]. In Rzanny et al [], HR subjects showed higher bilateral prefrontal (low molecular) PDE level and increased linewidth of the PDE components than controls, indicating increased membrane degradation processes and changes in the composition and fluidity of membrane phospholipids [Rzanny et al, ].…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%